1965
DOI: 10.1111/j.1365-2494.1965.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cocksfoot‐ and Tall Fescue‐dominant Swards for Out‐of‐season Production

Abstract: Swards based on a mixture of SI 70 tall fescue and S215 meadow fescue were very early in spring, gave high yields for conservation in mid-season and, rested from mid-August, gave good grazing in November-December. Under this treatment, the tall fescue assumed dominance, and the swards were persistent and remained productive. The digestibility of the tall fescue swards was always higher than that of swards based on cocksfoot with which they were compared. During spring and autumn the former sward was better gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…By then the pastures were rank (up to 40 cm tall) and plant density of both tall fescue and white clover had fallen. Sheep grazing began during the first summer (mid January) rather than the late autumn or winter as would have been desirable (Baker & Chard 1965), and over-grazing in the dry period further reduced plant dens\'ty, possibly through plant 'pulling' as has been observed with tall fescue at first grazing (B. R. Watkin, pers comm. ) The surviving tall fescue plants proved very persistent and no further decline in population was evident throughout the measurement years.…”
mentioning
confidence: 92%
“…By then the pastures were rank (up to 40 cm tall) and plant density of both tall fescue and white clover had fallen. Sheep grazing began during the first summer (mid January) rather than the late autumn or winter as would have been desirable (Baker & Chard 1965), and over-grazing in the dry period further reduced plant dens\'ty, possibly through plant 'pulling' as has been observed with tall fescue at first grazing (B. R. Watkin, pers comm. ) The surviving tall fescue plants proved very persistent and no further decline in population was evident throughout the measurement years.…”
mentioning
confidence: 92%
“…The growths were affected by decomposition processes connected with senescence (Marschner, 1995) and unfavourable weather conditions during winter. The great importance of winter weather conditions for yield and herbage quality was also described by Baker et al (1965), Balasko (1977), Prigge et al (1999), Wolf and Opitz von Boberfeld (2003), Wöhler (2003). Regarding the present results, the prevailing climatic conditions of the regions in Germany, Poland, Hungary and Czech Republic influenced DM decisively and were responsible DM (% of DM) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…DM yield and DOM of autumn saved herbage strongly depend on the length of the growing period before winter and the date of utilisation in winter (Gardner and Hunt, 1955;Gerrish et al, 1994), whereas the special climatic conditions during winter additionally influence the development of DM yield and DOM decisively (Baker at al., 1965;Balasko, 1977). A shorter growing period before winter utilisation improved DOM, but it led to lower DM yields at the same time (Opitz von Boberfeld and Wolf, 2002;Wolf and Opitz von Boberfeld, 2003).…”
mentioning
confidence: 99%
“…As noted by Baker et al (8) TF was more acceptable to cattle in early and late season. This is also evident from the VI data obtained in this experiment (Table 13).…”
Section: Animal Performancementioning
confidence: 62%
“…(8) Indicated that TF was more acceptable to cattle than orchardgrass in early and late season. Hughes (66) reported that although palatablllty of TF was not high, use of an electric fence resulted in efficient utilization at all times.…”
Section: Date Of Harvestmentioning
confidence: 99%